Thomas Aquinas and Francisco Suárez: Complementary Approaches in the Conformation of our Knowledge - Yangali Núñez, Oscar Edmundo (2021)
In the present work I propose that the epistemological positions of Thomas Aquinas and Francisco Suárez can be conceived as complementary insofar as we clarify how knowledge is formed for each one. In the first place, it is necessary to examine the principle of individuation in relation to abstraction in Aquinas. Second, the differences around the same issue are analyzed in Suárez. Finally, both positions are compared to establish two theories that can be conceived as two aspects that complete the same process of our knowledge and can form the basis of a laterepistemology in favor of the knowledge of reality.